(untitled) (Anclajes, 2023)
The first edition of Silvina Ocampo’s 1937 book, Viaje Olvidado, includes several handwritten, unpublished rewritings. Following our hypothesis, rather than corrections that restore meanings and certainties, they constitute a retraction, an intensified “return” to indeterminacy and ambiguity that characterizes the stories in the volume. To demonstrate this, we will analyze the author’s rewriting of four paradigmatic stories: “Cielo de claraboyas”, “La calle Sarandí”, “El retrato mal hecho” and “Los funámbulos”.